Development of Small-Molecule Cryptochrome Stabilizer Derivatives as Modulators of the Circadian Clock - Lee, Jae Wook (ChemMedChem, 2015)
Small-molecule probes have been playing prominent roles in furthering our understanding of the molecular underpinnings of the circadian clock. We previously discovered a carbazole derivative, KL001 (N-(3-(9H-carbazol-9-yl)-2-hydroxypropyl)-N-(furan-2-ylmethyl)methanesulfonamide), as a stabilizer of the clock protein cryptochrome (CRY). Herein we describe an extensive structure–activity relationship analysis of KL001 derivatives leading to the development of a highly active derivative: 2-(9H-carbazol-9-yl)-N-(2-chloro-6-cyanophenyl)acetamide (KL044). Subsequent 3D-QSAR analysis identified critical features of KL001 derivatives and provided a molecular-level understanding of their interaction with CRY. The electron-rich carbazole, amide/hydroxy linker, sulfonyl group, and electron-withdrawing nitrile moieties contribute to greater biological activity. The hydrogen bonding interactions with Ser394 and His357 as well as stronger CH–π interactions with Trp290 make KL044 a better binder than KL001. KL044 lengthened the circadian period, repressed Per2 activity, and stabilized CRY in reporter assays with roughly tenfold higher potency than KL001. Altogether, KL044 is a powerful chemical tool to control the function of the circadian clock through its action on CRY.